O-159 Uniform communication by nurses and midwives in anticipation of an IVF treatment. (30th June 2022) - Somers, S; Madoc, B; Bulteel, C; Cappon, S; Van Belle, E; De Beir, R; Stoop, D; De Sutter, P
Abstract: Study question: How do patients perceive the pre-IVF treatment communication by the nursing and midwifery team and how do they evaluate implemented optimization? Summary answer: Patient satisfaction with the pre-IVF treatment communication by the nursing and midwifery team improved from 86% to 98% after implementation of standardized written patient information. What is known already: Nurses are the main point of contact for patients undergoing medically assisted reproduction techniques (Applegarth et al., 2008). Morris (2001) suggested that infertility nurses could more specifically be involved in informative counselling in anticipation of the fertility treatment. Specific training for nurses and midwives would be required in order to achieve that central role in effective fertility counselling (Applegarth et al., 2012). However, little has been published in peer reviewed literature on how to assess and improve these pre-IVF treatment information sessions. Study design, size, duration: The pre-IVF communication by the nurse/midwife was assessed by female patients with a self-developed questionnaire (cohort 1). The nursing and midwifery team was subsequently informed about the results of the questionnaire and efforts were undertaken to optimise future patient communication. Four years later, a follow-up questionnaire assessed patient satisfaction about the intervention (cohort 2). Each cohort comprised fifty patients and nurses and midwives were blinded for patient participation to the study. Participants/materials, setting, methods: The study was performed at an academic fertility centre and was approved by the Investigational Review Board. Data were collected with SurveyMonkey (pre intervention) and REDCap (post intervention). A descriptive analysis of the cohorts and patient feedback was performed. The intervention consisted of (1) the optimization of patient information documents if needed (2) providing a training to the nursing and midwifery staff, and (3) a follow-up questionnaire in a second cohort of female fertility patients. Main results and the role of chance: The first questionnaire revealed that overall, patients were satisfied with the informative counselling session in anticipation of the IVF treatment. However, some patients indicated that they received a lot of information at once and that specific information that was of relevance for the further treatment (e.g. oocyte pick-up) was sometimes missed. Also, the data showed that not all patients received the same information. Therefore, all information that patients needed during an IVF treatment was gathered into a patient binder. It was supplemented with a timeline of the whole IVF trajectory, QR codes to movies explaining the administration of medication, and answers to common patients' questions. It was possible to individualize the content of the binder per patient. Ideally, patients received this binder before the informative counselling session so they could read the content in advance. The binder was developed by a member of the nursing and midwifery team and was reviewed by the medical, laboratory, and administrative staff. Then, the nursing and midwifery team was trained on the use of the patient binder. The follow-up questionnaire revealed that patient satisfaction with the pre-IVF treatment counselling was 98% after the optimization of patient documentation (compared to 86% before the optimization). Limitations, reasons for caution: Eligible patients were recruited by the treating physician. As no records were kept of the number of solicited patients for this study, no assessment of the response rate is possible. The cohorts were self-selected and limited in size and could therefore not reflect the general patient population. Wider implications of the findings: A patient questionnaire and follow-up is a useful tool for a centre specific assessment and improvement of pre-IVF nurse/midwife communication with patients. Clinics could make efforts to invest in complete and written information and ask colleagues of the nursing and midwifery team to be involved in its creation. Trial registration number: NCT04420169